2017
DOI: 10.1002/jcp.25881
|View full text |Cite
|
Sign up to set email alerts
|

Steady state peripheral blood provides cells with functional and metabolic characteristics of real hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs), which are located in the bone marrow, also circulate in cord and peripheral blood. Despite high availability, HSCs from steady state peripheral blood (SSPB) are little known and not used for research or cell therapy. We thus aimed to characterize and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Murine studies demonstrated HSC migration to ectopic niches via the circulation (Christensen et al, 2004;Wright et al, 2001). HSCs were detected in the blood of 12-to 18-week-old human fetuses (Gallacher et al, 2000), and long-term repopulating HSCs were demonstrated in adult human steady-state peripheral blood (Bourdieu et al, 2017;Brunet de la Grange et al, 2013). We now demonstrate the turnover of ''ectopic'' niche HSPCs from the circulating pool in humans.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 59%
“…Murine studies demonstrated HSC migration to ectopic niches via the circulation (Christensen et al, 2004;Wright et al, 2001). HSCs were detected in the blood of 12-to 18-week-old human fetuses (Gallacher et al, 2000), and long-term repopulating HSCs were demonstrated in adult human steady-state peripheral blood (Bourdieu et al, 2017;Brunet de la Grange et al, 2013). We now demonstrate the turnover of ''ectopic'' niche HSPCs from the circulating pool in humans.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 59%
“…In humans, the SP phenotype has been discovered in HSCs (hHSCs) isolated from the peripheral blood [34, 59], umbilical cord blood [35], and bone marrow [13].…”
Section: Side Population and Stem Cellsmentioning
confidence: 99%
“…The SP cells in hHSCs derived from peripheral blood were also reported to be CD34 + and CD38 − . These SP cells displayed greater proliferative capacity and generated more clonogenic progenitors during culturing and also showed greater engraftment capabilities in xenotransplantation studies [34, 59].…”
Section: Side Population and Stem Cellsmentioning
confidence: 99%
“…Nonetheless, despite the clinical efficiency of mPB in HCT and the global good tolerance of the mobilization regimen for the donor, PB mobilization can induce severe adverse effects in rare cases and nearly all donors experience inconveniences such as bone pain, headache, and nausea [5]. Therefore, as SSPB HSCs possess functional characteristics of real HSCs [6][7][8][9][10], they represent an easy and interesting source of HSCs for HCT, provided reliable ex vivo procedures to amplify HSC to numbers sufficient for an effective engraftment are developed. The ex vivo expansion of HSC without the loss of a marrow repopulating ability and long-term stem cell potential is a challenging question.…”
Section: Introductionmentioning
confidence: 99%